Beyond coherence: a DAC criteria review of Sri Lanka’s climate policy architecture - Chamara Senadeera; Abu Sadat Muhammad Sayem; Walter Leal Filho; Grace Farhat; Haruna Musa Moda; Ruvini Dissanayake (Regional Environmental Change, 2026)
Climate change is intensifying Sri Lanka’s exposure to multiple hazards, including floods, droughts, landslides, cyclones, coastal risks and heat stress, with growing consequences for livelihoods, infrastructure, public health and national development. This analysis evaluates whether Sri Lanka’s contemporary climate policy architecture is sufficiently coherent and operationally robust to support effective climate resilience. A qualitative policy analysis was undertaken of eight core national climate-related instruments, generated by analytically combining thirteen policy and institutional documents published between 2021 and 2025. The study employed NVivo-based content analysis and a structured benchmarking framework based on an adapted Organisation for Economic Co-operation and Development Development Assistance Committee framework, which assessed relevance, coherence, effectiveness, efficiency, equity and sustainability. The pilot coding process achieved an intercoder reliability score of 0.81, indicating strong agreement between coders. The findings indicate that Sri Lanka’s policy architecture performs strongly on relevance and coherence, with mean scores of 4.1 and 3.9, respectively, reflecting substantial strategic alignment with the country’s multi-hazard climate risk profile. However, effectiveness and efficiency remained moderate, with both recording mean scores of 3.1, while equity and gender considerations emerged as the weakest dimension at 3.0. Sustainability varied across instruments depending on the extent to which they incorporated operational monitoring, statutory review cycles and multi-year financing arrangements. Instruments with clearer SMART targets, operational monitoring, reporting and verification systems, designated institutional responsibilities and costed financing pathways performed more strongly than those relying on broad commitments or annualised budget structures. Overall, Sri Lanka’s principal climate governance challenge lies not in the absence of policy ambition, but in the incomplete institutionalisation of delivery systems needed to convert strategic coherence into measurable resilience outcomes. Aim of the study To critically evaluate the coherence and implementation robustness of Sri Lanka’s contemporary national climate policy architecture in order to determine whether strategic policy commitments are supported by adequate institutional design, financing arrangements, monitoring systems, equity safeguards and long-term sustainability in the context of escalating multi-hazard climate risks.

Health risk assessment of heavy metals in exposed workers of municipal waste recycling facility in Iran - Safiye Ghobakhloo; Gholam Reza Mostafaii; Amir Hossein Khoshakhlagh; Haruna Musa Moda; Agnieszka Gruszecka-Kosowska (Chemosphere, 2024)